1999
DOI: 10.1287/mksc.18.4.504
|View full text |Cite
|
Sign up to set email alerts
|

The Decomposition of Promotional Response: An Empirical Generalization

Abstract: Price promotions are used extensively in marketing for one simple reason—consumers respond. The sales increase for a brand on promotion could be due to consumers accelerating their purchases (i.e., buying earlier than usual and/or buying more than usual) and/or consumers switching their choice from other brands. Purchase acceleration and brand switching relate to the primary demand and secondary demand effects of a promotion. Gupta (1988) captures these effects in a single model and decomposes a brand's total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
308
5
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(341 citation statements)
references
References 52 publications
26
308
5
2
Order By: Relevance
“…Scriven et al (1999) concluded the opposite and found that the under 45's were consistently more sensitive to price change. A number of studies also showed insignificant or no effect of demographics on consumer price responsiveness (Bell et al 1999;Boatwright et al 2004;George et al 1996;Kim et al 1999;Scriven and Ehrenberg 2004).…”
Section: Segmentationmentioning
confidence: 99%
“…Scriven et al (1999) concluded the opposite and found that the under 45's were consistently more sensitive to price change. A number of studies also showed insignificant or no effect of demographics on consumer price responsiveness (Bell et al 1999;Boatwright et al 2004;George et al 1996;Kim et al 1999;Scriven and Ehrenberg 2004).…”
Section: Segmentationmentioning
confidence: 99%
“…Other recent studies of the impact of promotion on purchase behavior go beyond estimation of the "primitive" elasticities of incidence, choice and quantity to conduct meta-analyses of the response parameters themselves. Bell, Chiang and Padmanabhan (1999) use this approach to find that storability has a positive effect on primary demand response to promotions (quantity, but not incidence) as well as a positive effect on secondary demand, or brand choice.…”
Section: Rationale For Price Promotionmentioning
confidence: 99%
“…More specifically, much of the marketing research in this area focuses on differentiating between the impact of price promotion on: (1) volume or market share of a particular brand or variety and (2) overall store or category-level volume (Gupta 1988;Bell, Chiang and Padmanabhan 1999;Pauwels, Hanssens and Siddarth 2002;Chintagunta 2002). Given that the effect on share and consumer numbers are necessarily specified in a very simple way in the theoretical model, we develop a more general econometric model to test the impact of both tools (number of sale products and depth of discount) on product and store sales.…”
Section: Theoretical Model Of Price Promotions For Perishable Productsmentioning
confidence: 99%
“…This finding questions the supposition that the quantity consumers buy remains relatively constant across shopping occasions (cf. Bell, Chiang, & Padmanabhan, 1999;Ehrenberg, 1972Ehrenberg, /1988Gupta, 1988;Uncles et al, 1995).…”
Section: Discussionmentioning
confidence: 99%